Aberrant Cost–Benefit Integration During Effort-Based Decision Making Relates to Severity of Substance Use Disorders. (January 2020) - Stuppy-Sullivan, Allison M.; Buckholtz, Joshua W.; Baskin-Sommers, Arielle
Aberrant cost–benefit decision making is a key factor related to individual differences in the expression of substance use disorders (SUDs). Previous research highlights how delay-cost sensitivity affects variability in SUDs; however, other forms of cost–benefit decision making—effort-based choice—have received less attention. We administered the Effort Expenditure for Rewards Task (EEfRT) in an SUD-enriched community sample ( N = 80). Individuals with more severe SUDs were less likely to use information about expected value when deciding between high-effort, high-reward and low-effort, low-reward options. Furthermore, individuals whose severity of use was primarily related to avoiding aversive affective states and individuals with heightened sensitivity to delay costs during intertemporal decision making were the least sensitive to expected value signals when making decisions to engage in effortful behavior. Together, these findings suggest that individuals with more severe SUDs have difficulty integrating multiple decision variables to guide behavior during effort-based decision making.